Early mitigation of landslide prone areas with remote sensing and analysis of slope stability in ampera, south jayapura district, papua province. Issue 1 (March 2021) - Widodo, B T; Widoanindyawati, V; Widodo, B
Abstract: Ampera, located in the eastern slope of Cycloop Mountains, Papua Province had a landslide disaster on March 17, 2019. Landslides in Ampera is caused by the steep slope. Landslides occur due to lack of early mitigation which results in material loss and death. Early mitigation was carried out by remote sensing aimed at mapping landslide-prone areas in Ampera. The determination of landslide-prone areas is based on several parameters and weighting of remote sensing. The parameters are based on the provisions made by the author with secondary data. Weighting is used based on the results AHP method. Parameters and weighting using rainfall (44%), slope gradient (31%), NDVI (15%), slope water density (7%), and road density (3%). This parameter is processed into raster data which is then combined with weighting. The results, Ampera has a moderate to high vulnerability for landslides. Three high vulnerability area was made a modeling incision to determine safety factor value for slope stability. Modeling was done using characteristics of Podzolic Soil type, obtained from the Soil Distribution Map of Papua Province. Based on the results of the modeling, the average value of the safety factor of slope stability in three areas with high vulnerability is 0.5 (unstable).